The New Avant-Garde in Italy : Theoretical Debate and Poetic Practices - Picchione, John, 1949- (Book collections on Project MUSE., 2004)
This study suggests that some of the contentious views proposed by the neoavanguardia anticipated a wide range of issues that continue to be significant and pressing to this day.